Socio-economic inequalities in high blood pressure and additional risk factors for cardiovascular disease among older individuals in Colombia: Results from a nationally representative study (2020)
Background Studies in high-income countries have documented a consistent gradient between socio-economic status (SES) and high blood pressure (HBP), a key risk factor for cardiovascular disease (CVD). However, evidence from Latin American countries (LA) remains comparatively scarce and inconclusive. Data Data for 3,984 individuals came from a nationally representative survey of individuals aged 60 years or above in Colombia (Encuesta de Salud, Bienestar y Envejecimiento) (SABE) conducted in 2015. SES was measured by educational achievement and household assets. CVD risk factors included objectively measured HBP and body mass index (BMI), as well as behaviors (smoking, alcohol consumption, fruit and vegetables intake, and physical activity). Methods Bivariate methods and multivariate regression models were used to assess associations between SES with HBP as well as additional risk factors for CVD. Results Individuals with lower SES have significantly higher risk of suffering from HBP. Compared to those with no formal education, individuals with secondary or post-secondary education have a 37% lower risk of HBP (odds ratio [OR] = 0.63, P-value<0.001). Being in the highest asset quartile (most affluent) is associated with a 44% lower risk (OR = 56, P-value = 0.001) of HBP compared to those in the lowest asset quartile (most deprived). Individuals with lower SES are more likely to smoke, not engage in regular physical activity and not regularly consume fruits or vegetables. In contrast, individuals with higher SES are more likely to consume alcohol and, those with more assets, more likely to be obese. Conclusions Among older Colombians there exists a marked SES gradient in HBP as well as several additional risk factors for CVD. The results highlight the importance of a public health approach towards HBP and additional CVD risk factors that takes into account the specific conditions of older individuals, especially among disadvantaged groups.